Business cycle co-movements between South Africa and the BRIC countries - Çakır, Mustafa; Kabundi, A. (Routledge Journals, Taylor & Francis LTD, 2013)
This article examines the relationships between South African economy and the economies of the BRIC (Brazil, Russia, India and China). In particular, it identifies the nature and key features of the co-movement of South African business cycles with cycles of the BRIC countries. It uses the dynamic factor model to a set of 307 macroeconomic series during the period 1995Q2 to 2009Q4. We found significant evidence of synchronization between South Africa and the BRIC countries over the business cycle, although the magnitude of co-movement differs with each country. India portrays strong ties with South Africa over time. Moreover, Brazil, China and Russia lead South Africa in the long run, while India is contemporaneous. Further, the findings imply that the first two factors are BRICS factors while the third one is a US factor.
WOS: 000322213400008
Keywords: dynamic factor model; international business cycles; co-movement; BRICS